Elemental composition of ambient air particles in Taiyuan, China: evaluation of lifetime cancer and non-cancer risks. Issue 5 (27th May 2020) - Zhang, Xin; Bai, Xu; Li, Chenghuan; Li, Tian; Wang, Rihua; Zhao, Zhuohui; Norback, Dan
Abstract: Shanxi is a heavily polluted area in China. Our aim was to analyze the elemental concentration (71 elements) in ambient air in Taiyuan and evaluate cancer and non-cancer risks. Air was sampled in four urban sites and one rural site in the heating season (winter/spring) and summer season (totally 118 days sampling time). Mean total suspended particles (TSP) across all sampling sites were 248 µg/m 3 in summer and 478 µg/m 3 in winter. The heating season had higher levels of S, Pb, Br, Mn, Se, As, Ni, Cd, and Hg (23.3 µg/m 3, 821 ng/m 3, 725 ng/m 3, 460 ng/m 3, 79 ng/m 3, 65 ng/m 3, 34 ng/m 3, 17 ng/m 3, and 3.5 ng/m 3, respectively) than the summer season (9.6 µg/m 3, 276 ng/m 3, 138 ng/m 3, 283 ng/m 3, 0 ng/m 3, 21 ng/m 3, 21 ng/m 3, 6.8 ng/m 3, and 0 ng/m 3, respectively), except for Cr and Co, of which the levels were higher in summer. Many elements had a high correlation with the TSP level ( r = 0.70–0.96) and S ( r = 0.61–0.95). A health risk assessment demonstrated that Mn and Cr could have a risk of non-cancer effects. Estimated lifetime cancer risks (Ri >10 −6 ) were observed for As, Cd, Co, Cr, and Ni, indicating that cancer risks from air pollution were relatively high in Taiyuan.